Composition, injection molded article, powder coating material, and coated electric wire

The composition was prepared by adding polytetrafluoroethylene to the fluoropolymer containing tetrafluoroethylene, hexafluoropropylene and perfluoro(propylvinyl ether) units, which solved the problem of insufficient injection moldability in the prior art, and achieved excellent molding performance under high temperature and high load.

CN119768467APending Publication Date: 2025-04-04DAIKIN INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380061010.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-07-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to improve the injection moldability of fluorine-containing copolymers containing tetrafluoroethylene, hexafluoropropylene and perfluoro(propyl vinyl ether) units, and improve the physical properties of the injection molded body.

Method used

A composition is provided that contains polytetrafluoroethylene and a fluorine-containing copolymer, wherein the content of polytetrafluoroethylene is 0.03% to 0.30%, the fluorine-containing copolymer contains tetrafluoroethylene, hexafluoropropylene and perfluoro(propylvinyl ether) units, the content of hexafluoropropylene units is 8.5% to 11.2%, the content of perfluoro(propylvinyl ether) units is 0.5% to 2.0%, and has a melt flow rate of 13.0 g/10 minutes to 42.0 g/10 minutes.

Benefits of technology

Excellent injection moldability, coating moldability and wire coat moldability of the composition are achieved, and the molded body obtained has deformation resistance at high temperature and high load, stress cracking resistance, deformation resistance to tensile stress, and resistance to repeated stress loads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005279156560000091
    Figure BDA0005279156560000091
  • Figure BDA0005279156560000221
    Figure BDA0005279156560000221
  • Figure BDA0005279156560000341
    Figure BDA0005279156560000341
Patent Text Reader

Abstract

Provided is a composition containing polytetrafluoroethylene and a fluorine-containing copolymer, the content of the polytetrafluoroethylene in the composition being 0.03-0.30 mass% with respect to the mass of the composition, the fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units, and perfluoro (propyl vinyl ether) units, and the fluorine-containing copolymer being characterized in that: the content of the polytetrafluoroethylene in the composition is 0.03-0.30 mass% with respect to the mass of the composition; the content of hexafluoropropylene units in the fluorine-containing copolymer is 8.5% by mass to 11.2% by mass with respect to the total monomer units, the content of perfluoro (propyl vinyl ether) units in the fluorine-containing copolymer is 0.5% by mass to 2.0% by mass with respect to the total monomer units, and the melt flow rate at 372 DEG C is 13.0 g / 10 minutes to 42.0 g / 10 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a composition, an injection molded body, a powder coating, and a coated electric wire. Background Art

[0002] Patent document 1 describes a fluororesin composition, characterized in that it comprises polytetrafluoroethylene [PTFE] having a standard specific gravity of 2.15 to 2.30 and a tetrafluoroethylene / hexafluoropropylene copolymer [FEP], wherein the content of the PTFE is 0.01 to 3 parts by mass relative to 100 parts by mass of the FEP, and the content of alkali metals is less than 5 ppm relative to the solid content of the resin composition. The fluororesin composition is obtained by a method comprising the following steps: step (1), mixing an aqueous dispersion containing the FEP and an aqueous dispersion containing the PTFE, followed by precipitation, thereby obtaining a co-precipitated powder of the fluororesin; step (2), melt-extruding the co-precipitated powder; and step (3), stabilizing the unstable terminal groups of the PTFE and the FEP.

[0003] Patent document 2 describes a fluororesin composition, which is a fluororesin composition composed of 100 parts by mass of a tetrafluoroethylene / hexafluoropropylene copolymer and 0.01 to 3 parts by mass of polytetrafluoroethylene having a standard specific gravity of 2.15 to 2.30, characterized in that the fluororesin composition is obtained by mixing an aqueous dispersion composed of the tetrafluoroethylene / hexafluoropropylene copolymer and an aqueous dispersion composed of the polytetrafluoroethylene, followed by precipitation, and then melt-extruding after drying.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2009 / 044753

[0007] Patent Document 2: International Publication No. 2006 / 123694 Summary of the invention

[0008] Problems to be solved by the invention

[0009] An object of the present disclosure is to provide a composition having excellent injection moldability, coating film moldability, and wire coating moldability, and capable of obtaining a molded product having excellent deformation resistance to high temperature and high load, stress crack resistance, deformation resistance to tensile stress, and resistance to repeated stress loads.

[0010] Means for solving problems

[0011] According to the present disclosure, a composition is provided, which is a composition containing polytetrafluoroethylene and a fluorine-containing copolymer, wherein the content of the polytetrafluoroethylene in the composition is 0.03% by mass to 0.30% by mass relative to the mass of the composition, the fluorine-containing copolymer contains tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units, the content of the hexafluoropropylene units in the fluorine-containing copolymer is 8.5% by mass to 11.2% by mass relative to all monomer units, the content of the perfluoro(propyl vinyl ether) units is 0.5% by mass to 2.0% by mass relative to all monomer units, and the melt flow rate at 372°C is 13.0 g / 10 min to 42.0 g / 10 min.

[0012] Effects of the Invention

[0013] According to the present disclosure, a composition can be provided which has excellent injection moldability, coating film moldability, and wire coating moldability, and can obtain a molded product having excellent deformation resistance to high temperature and high load, stress crack resistance, deformation resistance to tensile stress, and resistance to repeated stress loads. DETAILED DESCRIPTION

[0014] Hereinafter, specific embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to the following embodiments.

[0015] The composition of the present disclosure contains polytetrafluoroethylene and a fluorine-containing copolymer.

[0016] Patent Document 1 proposes the above-mentioned fluororesin composition for the purpose of providing a fluororesin composition that is less likely to cause molding defects even when high-speed molding is performed in coating extrusion molding within a relatively wide molding temperature range and that can produce an electric wire, particularly a foamed electric wire, having excellent surface smoothness. In addition, Patent Document 2 proposes the above-mentioned fluororesin composition for the purpose of improving moldability in melt extrusion molding.

[0017] However, there has been no research on means for improving the injection moldability of fluorinated copolymers containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units. Also, there has been no research on improving the physical properties of injection molded products.

[0018] In view of such a situation, the purpose of the present disclosure is to provide a composition that can improve the injection moldability of a fluorinated copolymer containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units, and thereby obtain a molded body having excellent deformation resistance to high temperature and high load. In addition, the composition of the present disclosure has excellent coating moldability and wire coating moldability. Furthermore, by using the composition of the present disclosure, a molded body having excellent stress crack resistance, deformation resistance to tensile stress, and resistance to repeated stress loads can be obtained.

[0019] (Polytetrafluoroethylene)

[0020] The composition disclosed herein contains polytetrafluoroethylene (PTFE). The composition disclosed herein contains a limited amount of PTFE, and as described later, contains a fluorinated copolymer whose composition and melt flow are limited, so it can be easily molded by injection molding, and then an injection molded body with excellent aesthetics and excellent deformation resistance to high temperature and high load can be obtained. In addition, the coating moldability and wire coating moldability of the composition disclosed herein are also excellent. And then, by using the composition disclosed herein, a molded body with excellent stress crack resistance, deformation resistance to tensile stress, and resistance to repeated stress loads can be obtained.

[0021] The PTFE contained in the composition of the present disclosure may be a PTFE with non-melt processability or a PTFE with melt processability. As the PTFE, the PTFE with non-melt processability is preferred from the viewpoints of further improving the injection moldability of the composition and the deformation resistance of the injection molded body, improving the coating moldability and wire coating moldability, and improving the stress cracking resistance, deformation resistance to tensile stress, and resistance to repeated stress loads of the molded body.

[0022] Non-melt-processibility refers to the property that the melt flow rate cannot be determined at a temperature above the melting point of PTFE according to ASTM D 1238 and D 2116.

[0023] PTFE can be PTFE with fibrillation or non-fibrillation. As PTFE, from the injection moldability of the composition and the deformation resistance of the injection molded body, the coating moldability of the wire coating moldability, and the stress cracking resistance of the molded body, the deformation resistance to tensile stress, and the resistance to repeated stress loads, the PTFE with fibrillation is preferred.

[0024] The presence or absence of fibrillation can be judged by "paste extrusion", which is a representative method for molding a powder made from a polymer of TFE, i.e., "high molecular weight PTFE powder". This is because, usually, when paste extrusion can be performed, high molecular weight PTFE has fibrillation. In the case where the unfired molded product obtained by paste extrusion does not have substantial strength or elongation, for example, in the case where the elongation is 0% and it breaks if stretched, it can be considered as not having fibrillation.

[0025] The standard specific gravity (SSG) of PTFE is preferably 2.15 to 2.25, more preferably 2.20 or less. By making the standard specific gravity of PTFE within the above range, the injection moldability of the composition and the deformation resistance of the injection molded body can be further improved, and the coating moldability and wire coating moldability, as well as the stress cracking resistance, deformation resistance to tensile stress, and resistance to repeated stress loads of the molded body can also be improved.

[0026] The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895-89.

[0027] The melting point of PTFE is preferably 320° C. or higher, more preferably 323° C. or higher, and further preferably 325° C. or higher, and is preferably 337° C. or lower, more preferably 335° C. or lower, and further preferably 333° C. or lower.

[0028] The melting point (secondary melting point) of PTFE can be determined as follows: using a differential scanning calorimeter, the temperature is first increased from 230°C to 380°C at a heating rate of 10°C / min, then cooled from 380°C to 230°C at a cooling rate of 10°C / min, and then the temperature is increased from 230°C to 380°C for a second time at a heating rate of 10°C / min, and the melting curve peak generated during the second heating process is recorded, and the temperature corresponding to the peak top is determined.

[0029] PTFE may be a TFE homopolymer containing only TFE units, or may be a modified PTFE containing TFE units and a modifying monomer unit copolymerizable with TFE.

[0030] Examples of the modifying monomer include perfluoroolefins such as hexafluoropropylene; chlorofluoroolefins such as chlorotrifluoroethylene; hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride; fluoroalkyl vinyl ethers; fluoroalkyl allyl ethers; perfluoroalkylethylenes; ethylene; and the like.

[0031] The content of the modified monomer unit in PTFE is preferably 0 to 1.0% by mass, more preferably 0.5% by mass or less, further preferably 0.2% by mass or less, particularly preferably 0.1% by mass or less, based on all monomer units constituting PTFE.

[0032] The content of the TFE unit in PTFE is preferably 100 to 99.0% by mass, more preferably 99.5% by mass or more, further preferably 99.8% by mass or more, particularly preferably 99.9% by mass or more, based on all monomer units constituting PTFE.

[0033] The content of each monomer constituting PTFE can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the types of monomers.

[0034] The PTFE used in the composition obtained by mixing PTFE and the fluorine-containing copolymer may be PTFE dispersed in an aqueous dispersion or in the form of PTFE powder. The PTFE powder may be PTFE fine powder or PTFE molding powder.

[0035] In one embodiment, primary particles of PTFE dispersed in an aqueous dispersion may be used. The average primary particle size of PTFE is preferably 10 nm to 800 nm, more preferably 50 nm or more, and more preferably 500 nm or less.

[0036] Regarding the average primary particle size of PTFE, for an aqueous dispersion diluted with water to a solid content of 0.22% by mass, the transmittance of projected light with a wavelength of 500 nm relative to a unit length is measured, and the oriented diameter in the transmission electron microscope photograph is pre-measured. The average primary particle size of the PTFE based on the obtained number-based length can be determined based on a calibration curve of the above-mentioned transmittance.

[0037] In one embodiment, secondary particles of PTFE may be used. The secondary particles of PTFE are particles formed by agglomeration of primary particles of PTFE. The average secondary particle size of PTFE is preferably 1 μm to 2000 μm.

[0038] The secondary particle size of PTFE can be measured in accordance with ASTM D 4895.

[0039] (Fluorinated copolymer)

[0040] The fluorinated copolymer contained in the composition of the present disclosure is a melt-processable fluororesin. Melt-processability means that the polymer can be melted and processed using existing processing equipment such as an extruder and an injection molding machine.

[0041] The fluorine-containing copolymer contained in the composition of the present disclosure contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units, and perfluoro(propyl vinyl ether) (PPVE) units.

[0042] The content of the HFP unit of the fluorinated copolymer is 8.5% to 11.2% by mass relative to all monomer units constituting the fluorinated copolymer, preferably 8.8% by mass or more, more preferably 9.0% by mass or more, further preferably 9.1% by mass or more, further preferably 9.2% by mass or more, further preferably 9.3% by mass or more, particularly preferably 9.4% by mass or more, particularly preferably 9.5% by mass or more, most preferably 9.7% by mass or more, preferably 11.1% by mass or less, more preferably 11.0% by mass or less, further preferably 10.9% by mass or less, particularly preferably 10.8% by mass or less. If the content of the HFP unit is too small, when the composition is molded by injection molding to obtain an injection molded body, the injection molded body is easily damaged. In addition, if the content of the HFP unit is too small, excellent coating moldability and wire coating moldability cannot be obtained, and a molded body with excellent stress cracking resistance cannot be obtained. If the content of the HFP unit is too much, it is difficult to take out the injection molded body from the mold when the composition is molded by injection molding, and the productivity of the injection molded body is poor. In addition, if the content of the HFP unit is too much, a molded body with excellent resistance to deformation at high temperature and high load and resistance to repeated stress loads cannot be obtained.

[0043] The content of the PPVE unit of the fluorinated copolymer is 0.5% to 2.0% by mass relative to all the monomer units constituting the fluorinated copolymer, preferably 0.6% by mass or more, more preferably 0.7% by mass or more, preferably 1.9% by mass or less, more preferably 1.8% by mass or less, further preferably 1.7% by mass or less, and particularly preferably 1.6% by mass or less. If the content of the PPVE unit is too small, delamination is likely to occur when the composition is molded by injection molding to obtain an injection molded body. In addition, if the content of the PPVE unit is too small, excellent wire coating moldability cannot be obtained, and a molded body with excellent stress cracking resistance cannot be obtained. If the content of the PPVE unit is too much, fibrous streaks are likely to occur in the injection molded body when the composition is molded by injection molding to obtain an injection molded body. In addition, if the content of the PPVE unit is too much, it is difficult to remove the injection molded body from the mold when the composition is molded by injection molding, and the productivity of the injection molded body is poor. Furthermore, when the content of the PPVE unit is too large, a molded product having excellent deformation resistance to high temperature and high load and excellent deformation resistance to tensile stress cannot be obtained.

[0044] The content of the TFE unit in the fluorinated copolymer is preferably 86.8% by mass or more, more preferably 86.9% by mass or more, further preferably 87.0% by mass or more, further preferably 87.1% by mass or more, further preferably 87.2% by mass or more, particularly preferably 87.4% by mass or more, and most preferably 87.6% by mass or more, and is preferably 91.0% by mass or less, more preferably 90.7% by mass or less, further preferably 90.3% by mass or less, further preferably 89.9% by mass or less, further preferably 90.0% by mass or less, particularly preferably 89.8% by mass or less, and most preferably 89.6% by mass or less, relative to all monomer units constituting the fluorinated copolymer. In addition, the content of the TFE unit may be selected so that the total content of the HFP unit, the PPVE unit, the TFE unit, and other monomer units is 100% by mass.

[0045] As long as the fluorinated copolymer contains the above three kinds of monomer units, it may be a copolymer containing only the above three kinds of monomer units or a copolymer containing the above three kinds of monomer units and other monomer units.

[0046] The other monomer is not particularly limited as long as it is a monomer copolymerizable with TFE, HFP and PPVE, and may be a fluorine-containing monomer or a non-fluorine-containing monomer.

[0047] The fluorine-containing monomer is preferably selected from the group consisting of chlorotrifluoroethylene, vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH2=CZ 1 (CF2) n Z 2 (Where Z 1 H or F, Z 2 is H, F or Cl, n is an integer from 1 to 10), CF2=CF-ORf 1 (Where Rf 1 Perfluoro(alkyl vinyl ether) [PAVE] (excluding PPVE) represented by a perfluoroalkyl group having 1 to 8 carbon atoms), CF2=CF-O-CH2-Rf 2 (Where Rf 2 At least one selected from the group consisting of an alkyl perfluorovinyl ether derivative represented by a perfluoroalkyl group having 1 to 5 carbon atoms, perfluoro-2,2-dimethyl-1,3-dioxole [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxolane [PMD].

[0048] As CH2=CZ 1 (CF2) n Z 2The monomers shown include CH2=CFCF3, CH2=CH-C4F9, CH2=CH-C6F 13 , CH2=CF-C3F6H, etc.

[0049] As CF2=CF-ORf 1 The perfluoro(alkyl vinyl ether) shown here includes CF2=CF-OCF3, CF2=CF-OCF2CF3 and the like.

[0050] As the non-fluorine-containing monomer, there can be mentioned hydrocarbon monomers that can be copolymerized with TFE, HFP and PPVE. As the hydrocarbon monomer, there can be mentioned, for example, olefins such as ethylene, propylene, butylene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl isobutyrate, vinyl valerate, vinyl pivalate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl versatate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl cyclohexanecarboxylate, vinyl monochloroacetate , vinyl adipate, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecylenate, vinyl hydroxyacetate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, vinyl hydroxycyclohexanecarboxylate and other vinyl esters; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, cyclohexyl allyl ether; alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, cyclohexyl allyl ester, etc.

[0051] As the non-fluorine-containing monomer, a hydrocarbon monomer containing a functional group copolymerizable with TFE, HFP and PPVE may also be used. Examples of hydrocarbon monomers containing functional groups include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether; non-fluorine-containing monomers having a glycidyl group such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorine-containing monomers having an amino group such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorine-containing monomers having an amide group such as (meth)acrylamide and hydroxymethyl acrylamide; bromine-containing olefins, iodine-containing olefins, bromine-containing vinyl ethers, and iodine-containing vinyl ethers; non-fluorine-containing monomers having a nitrile group, etc.

[0052] The content of other monomer units in the fluorinated copolymer is preferably 0 to 4.2 mass %, more preferably 2.8 mass % or less, further preferably 1.0 mass % or less, particularly preferably 0.5 mass % or less, most preferably 0.1 mass % or less, based on the total monomer units constituting the fluorinated copolymer.

[0053] The melt flow rate (MFR) of the fluorinated copolymer is 13.0 g / 10 min to 42.0 g / 10 min, preferably 14.0 g / 10 min or more, more preferably 15.0 g / 10 min or more, further preferably 17.0 g / 10 min or more, still further preferably 18.0 g / 10 min or more, still further preferably 19.0 g / 10 min or more, particularly preferably 21.0 g / 10 min or more, particularly preferably 22.0 g / 10 min or more, most preferably 23.0 g / 10 min or more, and is preferably 41.0 g / 10 min or less, more preferably 40.0 g / 10 min or less, further preferably 39.0 g / 10 min or less, further preferably 38.0 g / 10 min or less, particularly preferably 37.0 g / 10 min or less, and most preferably 36.5 g / 10 min or less. If the MFR is too low, flow marks are likely to occur when the composition is molded by injection molding to obtain an injection molded body, and delamination is likely to occur. In addition, if the MFR is too low, excellent coating moldability and wire coating moldability cannot be obtained, and a molded body with excellent deformation resistance to tensile stress cannot be obtained. If the MFR is too high, fibrous streaks are likely to occur in the injection molded body when the composition is molded by injection molding to obtain an injection molded body. In addition, if the MFR is too high, excellent coating moldability and wire coating moldability cannot be obtained, and a molded body with excellent stress cracking resistance cannot be obtained.

[0054] In the present disclosure, the melt flow rate is a value obtained as the mass (g / 10 minutes) of a polymer flowing out from a die having an inner diameter of 2 mm and a length of 8 mm at 372° C. and a load of 5 kg per 10 minutes using a melt flow indexer G-01 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ASTM D-1238.

[0055] The MFR can be adjusted by adjusting the type and amount of the polymerization initiator, the type and amount of the chain transfer agent, etc., used when polymerizing the monomers.

[0056] The fluorinated copolymer may or may not have a carbonyl-containing terminal group, -CF=CF2 or -CH2OH. In one embodiment of the fluorinated copolymer, the total number of carbonyl-containing terminal groups, -CF=CF2 and -CH2OH is relative to every 10 6The number of carbon atoms in the main chain is not more than 90. The total number of carbonyl-containing terminal groups, -CF=CF2 and -CH2OH can be adjusted, for example, by appropriate selection of the type of polymerization initiator or chain transfer agent, or by wet heat treatment or fluorination treatment of the fluorinated copolymer described later.

[0057] Examples of carbonyl-containing terminal groups include -COF, -COOH, -COOR (R is an alkyl group), -CONH2, and -O(C=O)OR (R is an alkyl group). The type of the alkyl group (R) possessed by -COOR and -O(C=O)OR is determined by the polymerization initiator and chain transfer agent used in the manufacture of the fluorinated copolymer, and is, for example, an alkyl group having 1 to 6 carbon atoms such as -CH3.

[0058] The fluorinated copolymer may or may not have -CF2H. In one embodiment of the fluorinated copolymer, the amount of -CF2H is relative to every 10 6 The number of carbon atoms in the main chain is not less than 50. The number of -CF2H can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by wet heat treatment or fluorination treatment of the fluorinated copolymer described later.

[0059] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.

[0060] The number of functional groups is specifically determined by the following method. First, the fluorinated copolymer is formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.30 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluorinated copolymer and a differential spectrum from a background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the fluorinated copolymer relative to each 1×10 6 The number of functional groups N per carbon atom.

[0061] N=I×K / t(A)

[0062] I: Absorbance

[0063] K: Correction coefficient

[0064] t: film thickness (mm)

[0065] For reference, absorption frequencies, molar absorption coefficients, and correction coefficients for some functional groups are shown in Table 1. The molar absorption coefficients were determined from FT-IR measurement data of low-molecular model compounds.

[0066] [Table 1]

[0067] Table 1

[0068]

[0069] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm2) lower than the absorption frequencies of -CF2H, -COF, free -COOH, and bound -COOH, -COOCH3, and -CONH2 shown in the table, respectively. -1 ).

[0070] For example, the functional group number of -COF is the absorption frequency 1883 cm due to -CF2COF. -1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF -1 The total number of functional groups found from the absorption peak at .

[0071] Alternatively, the number of -CF2H groups can be measured using a nuclear magnetic resonance apparatus at a temperature of (melting point of the polymer + 20)°C. 19 In F-NMR measurement, it was determined from the peak integral value of -CF2H group.

[0072] Functional groups such as -CF2H groups are functional groups present at the main chain ends or side chain ends of the fluorinated copolymer and functional groups present in the main chain or in the side chain. These functional groups are introduced into the fluorinated copolymer, for example, by a chain transfer agent or a polymerization initiator used when manufacturing the fluorinated copolymer. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain ends of the fluorinated copolymer. In addition, by polymerizing a monomer having a functional group, the above-mentioned functional group is introduced into the side chain ends of the fluorinated copolymer.

[0073] By subjecting the fluorinated copolymer having such functional groups to a treatment such as a wet heat treatment, a fluorination treatment, etc., a fluorinated copolymer having the number of functional groups within the above range can be obtained.

[0074] The melting point of the fluorinated copolymer is preferably from 220°C to 290°C, more preferably from 240°C to 280°C, from the viewpoint of further improving the injection moldability of the composition.

[0075] The melting point of the fluorinated copolymer can be measured using a differential scanning calorimeter [DSC].

[0076] The fluorinated copolymer can also be produced by any polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. In these polymerization methods, various conditions such as temperature and pressure, polymerization initiator, chain transfer agent, solvent, and other additives can be appropriately set according to the desired composition and amount of the fluorinated copolymer.

[0077] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical initiator can be used.

[0078] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, and the following may be cited as representative examples:

[0079] Dialkyl peroxycarbonates such as di-n-propyl peroxydicarbonate, di-isopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate;

[0080] Peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate;

[0081] Dialkyl peroxides such as di-tert-butyl peroxide;

[0082] Di[fluoro(or chlorofluoro)acyl]peroxides; etc.

[0083] Examples of the di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group or a fluorochloroalkyl group).

[0084] Examples of the di[fluoro(or chlorofluoro)acyl]peroxides include di(ω-hydroperfluorohexanoyl)peroxide, di(ω-hydro-dodecafluoroheptanoyl)peroxide, di(ω-hydro-tetrafluorooctanoyl)peroxide, di(ω-hydro-hexafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluorovaleranoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, and di(ω-chloro-hexafluorobutyryl)peroxide. , di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetrafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecanoyl)peroxide, di(pentachlorotetrafluorodecanoyl)peroxide, di(undecachlorotriacontanoyl)peroxide, and the like.

[0085] As the water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, etc., tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. It can also contain a reducing agent such as sulfites, and its amount can be 0.1 to 20 times that of the peroxide.

[0086] If use oil-soluble free radical polymerization initiator as polymerization initiator, then can avoid generating-COF and-COOH, can easily by the total amount of-COF and-COOH of fluorinated copolymer be adjusted to above-mentioned scope, therefore preferably.In addition, if use oil-soluble free radical polymerization initiator, then have also easily by carbonyl-containing terminal group and-CH2OH be adjusted to the tendency of above-mentioned scope.Particularly, preferably by using the suspension polymerization of oil-soluble free radical polymerization initiator to manufacture fluorinated copolymer.As oil-soluble free radical polymerization initiator, preferably select at least one in the group consisting of dialkyl peroxycarbonate and two [fluorine (or chlorine) acyl] peroxide, more preferably select at least one in the group consisting of di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate and two (ω-hydrogen-dodecanoyl) peroxide.

[0087] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; 3-fluorobenzotrifluoride, etc. The amount added can vary depending on the chain transfer constant of the compound used, and is usually used in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of the solvent.

[0088] For example, when dialkyl peroxycarbonates, di[fluoro(or chlorofluoro)acyl]peroxides, etc. are used as polymerization initiators, the molecular weight of the obtained fluorinated copolymer becomes too high, and it is sometimes difficult to adjust the desired melt flow rate, but a chain transfer agent can be used to adjust the molecular weight. It is particularly preferred to manufacture the fluorinated copolymer by suspension polymerization using a chain transfer agent such as alcohols and an oil-soluble free radical polymerization initiator.

[0089] Examples of the solvent include water, a mixed solvent of water and alcohol, etc. Alternatively, a monomer used for polymerization of the fluorinated copolymer may be used as the solvent.

[0090] In suspension polymerization, in addition to water, fluorine-based solvents can also be used. As fluorine-based solvents, hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl, etc.; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3, etc.; perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, etc. perfluoroalkanes, etc., among which perfluoroalkanes are preferred. From the aspects of suspensibility and economy, the amount of fluorine-based solvent used is preferably 10 to 100 parts by mass relative to 100 parts by mass of the solvent.

[0091] The polymerization temperature is not particularly limited and may be 0° C. to 100° C. In addition, when the decomposition rate of the polymerization initiator is too fast, such as when dialkyl peroxycarbonates, di[fluoro(or chlorofluoro)acyl]peroxides, etc. are used as the polymerization initiator, it is preferred to adopt a relatively low polymerization temperature such as a range of 0° C. to 35° C.

[0092] The polymerization pressure is appropriately determined according to other polymerization conditions such as the type of solvent used, the amount of solvent, vapor pressure, polymerization temperature, etc., and can generally be 0 MPaG to 9.8 MPaG. The polymerization pressure is preferably 0.1 MPaG to 5 MPaG, more preferably 0.5 MPaG to 2 MPaG, and further preferably 0.5 MPaG to 1.5 MPaG. In addition, when the polymerization pressure is 1.5 MPaG or more, the production efficiency can be improved.

[0093] As the additive in the polymerization, for example, a suspension stabilizer can be cited. As a suspension stabilizer, as long as it is an existing known suspension stabilizer, there is no particular limitation, and methylcellulose, polyvinyl alcohol, etc. can be used. If a suspension stabilizer is used, the suspended particles generated by the polymerization reaction are stably dispersed in the aqueous medium, so even if a reaction tank made of SUS that is not subjected to anti-adhesion treatments such as glass lining is used, the suspended particles are not easily attached to the reaction tank. Therefore, a reaction tank that withstands high pressure can be used, so polymerization under high pressure can be carried out, and production efficiency can be improved. In contrast, when polymerization is carried out without using a suspension stabilizer, if a reaction tank made of SUS that is not subjected to anti-adhesion treatment is used, the suspended particles are likely to adhere and reduce production efficiency. The concentration of the suspension stabilizer relative to the aqueous medium can be appropriately adjusted according to the conditions.

[0094] In the case of obtaining an aqueous dispersion containing a fluoropolymer by polymerization, the dry fluoropolymer can be recovered by precipitating, cleaning, and drying the fluoropolymer contained in the aqueous dispersion. In addition, in the case of obtaining a fluoropolymer in the form of a slurry by polymerization, the dry fluoropolymer can be recovered by taking out the slurry from the reaction vessel and cleaning and drying. By drying, the fluoropolymer can be recovered in the form of a powder.

[0095] The fluorinated copolymer obtained by polymerization can be formed into pellets. There is no particular limitation on the molding method for forming the pellets, and a conventionally known method can be used. For example, there can be cited a method in which the fluorinated copolymer is melt-extruded using a single-screw extruder, a twin-screw extruder, or a tandem extruder, and the fluorinated copolymer is cut into a predetermined length to form pellets. The extrusion temperature during melt extrusion needs to be changed according to the melt viscosity and the manufacturing method of the fluorinated copolymer, and is preferably the melting point of the fluorinated copolymer + 20°C to the melting point of the fluorinated copolymer + 140°C. There is no particular limitation on the cutting method of the fluorinated copolymer, and conventionally known methods such as a wire cutting method, a heat cutting method, an underwater cutting method, and a sheet cutting method can be used. The volatile components in the pellets can also be removed by heating the obtained pellets (degassing treatment). The obtained pellets can also be treated by contacting with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.

[0096] The fluorinated copolymer obtained by polymerization can also be heated to a temperature of 100° C. or more in the presence of air and water (wet heat treatment). As a method for wet heat treatment, for example, the following method can be cited: using an extruder, while supplying air and water, the fluorinated copolymer obtained by polymerization is melted and extruded. By wet heat treatment, thermally unstable functional groups such as -COF and -COOH of the fluorinated copolymer can be converted into thermally relatively stable -CF2H. In addition to air and water, the conversion reaction to -CF2H can be promoted by heating the fluorinated copolymer in the presence of an alkali metal salt. However, it should be noted that, depending on the use of the fluorinated copolymer, contamination caused by alkali metal salts should be avoided.

[0097] The fluorinated copolymer obtained by polymerization may or may not be fluorinated. The fluorinated copolymer which has not been fluorinated may be contacted with a fluorinated compound. The fluorinated copolymer may be converted into thermally extremely stable -CF3 by fluorination, including terminal groups containing carbonyl groups, thermally unstable functional groups such as -CH2OH, and thermally relatively stable functional groups such as -CF2H.

[0098] The fluorine-containing compound is not particularly limited, and a fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. As the above-mentioned fluorine radical source, F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogens (such as IF5, ClF3), etc. can be cited.

[0099] The fluorine free radical source such as F2 gas can be 100% concentration, but from the aspect of safety, it is preferably mixed with an inert gas and diluted to 5% to 50% by mass for use, and more preferably diluted to 15% to 30% by mass for use. As the above-mentioned inert gas, nitrogen, helium, argon, etc. can be cited, and nitrogen is preferred from the aspect of economy.

[0100] The conditions of the fluorination treatment are not particularly limited, and the fluorinated copolymer in a molten state may be brought into contact with the fluorinated compound, but it may be generally carried out at a temperature below the melting point of the fluorinated copolymer, preferably at 20°C to 220°C, and more preferably at 100°C to 200°C. The above-mentioned fluorination treatment is generally carried out for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the fluorinated copolymer that has not been fluorinated is brought into contact with fluorine gas (F2 gas).

[0101] (Composition of the composition)

[0102] The content of PTFE in the composition is 0.03% to 0.30% by mass relative to the mass of the composition, preferably more than 0.04% by mass, more preferably more than 0.05% by mass, preferably less than 0.25% by mass, more preferably less than 0.20% by mass, further preferably less than 0.19% by mass, further preferably less than 0.17% by mass, further preferably less than 0.15% by mass, particularly preferably less than 0.13% by mass, most preferably less than 0.12% by mass. If the content of PTFE is too little, then in the case where the composition is molded by injection molding to obtain an injection molded body, stratification is easily produced. In addition, if the content of PTFE is too little, a molded body with excellent resistance to deformation at high temperature and high load and to repeated stress loads cannot be obtained. If the content of PTFE is too much, then in the case where the composition is molded by injection molding to obtain an injection molded body, fibrous stripes are easily produced in the injection molded body. On the other hand, when the content of PTFE is too large, excellent coating film moldability and electric wire coating moldability cannot be obtained, and a molded body excellent in stress crack resistance cannot be obtained.

[0103] The composition may also contain other components different from PTFE and the above-mentioned fluorinated copolymer. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet light absorbers, antioxidants, foaming agents, fragrances, oils, softeners, dehydrofluorination agents, etc.

[0104] As fillers, for example, silicon dioxide, kaolin, clay, organic clay, talc, mica, aluminum oxide, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, glass fibers, etc. can be cited. As conductive agents, carbon black, etc. can be cited. As plasticizers, dioctyl phthalate, pentaerythritol, etc. can be cited. As processing aids, carnauba wax, sulfone compounds, low molecular weight polyethylene, fluorine-based additives, etc. can be cited. As dehydrofluorination agents, organic onium, amidines, etc. can be cited.

[0105] In addition, other polymers other than PTFE and the above-mentioned fluorinated copolymers may be used as the above-mentioned other components. Examples of other polymers include fluororesins, fluororubbers, and non-fluorinated polymers other than PTFE and the above-mentioned fluorinated copolymers.

[0106] The method for producing the composition includes: a method of dry mixing PTFE and a fluorinated copolymer; a method of pre-mixing PTFE and a fluorinated copolymer using a mixer and then melt-kneading them using a kneader, a melt extruder, etc.; a method of preparing an aqueous dispersion containing PTFE and a fluorinated copolymer and co-precipitating PTFE and the fluorinated copolymer; etc.

[0107] It is also possible to prepare a composition (masterbatch) containing PTFE and a fluorinated copolymer and containing more PTFE, and then mix the obtained composition with the fluorinated copolymer to manufacture the composition. As a method for manufacturing the composition (masterbatch), it is possible to cite: a method in which PTFE and the fluorinated copolymer are mixed in advance with a mixer, followed by melt mixing with a kneader, a melt extruder, etc.; a method in which an aqueous dispersion containing PTFE and a fluorinated copolymer is prepared, and PTFE and the fluorinated copolymer are coprecipitated; etc. As a method for mixing the obtained composition (masterbatch) with a fluorinated copolymer, it is possible to cite, for example, a method in which the two are mixed in a dry manner; a method in which the two are melt mixed using a kneader, a melt extruder, etc.; etc.

[0108] After preparing the composition containing PTFE and the fluorinated copolymer, the obtained composition may be subjected to a wet heat treatment or a fluorination treatment. The wet heat treatment and the fluorination treatment of the composition may be carried out by the same method as the wet heat treatment and the fluorination treatment of the fluorinated copolymer.

[0109] The form of the composition is not particularly limited, and may be powder, pellets, or the like.

[0110] (Molding and use of composition)

[0111] The composition of the present disclosure can be used as a molding material, and can be particularly suitable for use as a molding material used in an injection molding method. By molding the composition of the present disclosure, a molded body can be obtained. The molded body containing the composition of the present disclosure has excellent aesthetics and excellent deformation resistance to high temperature and high load.

[0112] The composition disclosed in the present invention can also be used as a powder coating. In the case where the composition is obtained in the form of a powder by the above-mentioned manufacturing method, the obtained powder can be directly used as a powder coating. In the case where the composition obtained by the above-mentioned manufacturing method is not a powder, for example, after the composition is manufactured, the obtained composition is compressed into a sheet with a roller, and crushed and classified by a pulverizer, thereby manufacturing a powder coating. The average particle size of the powder coating is preferably 10μm to 1000μm. Powder coatings are usually applied to the object to be coated and then heated and fired to form a film. The coating film obtained by such construction can be used for various purposes such as a corrosion-resistant lining.

[0113] The method for molding the composition is not particularly limited, and injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, roto-lining molding, etc. can be cited. As a molding method, among them, extrusion molding, compression molding, injection molding or transfer molding are preferred. From the aspect of being able to produce a molded body with high productivity, injection molding, extrusion molding or transfer molding are more preferred, and injection molding is further preferred. That is, as a molded body, an extrusion molded body, a compression molded body, an injection molded body or a transfer molded body are preferred. From the aspect of being able to produce with high productivity, injection molded bodies, extrusion molded bodies or transfer molded bodies are more preferred, and injection molded bodies are further preferred. By molding the composition of the present disclosure by injection molding, a beautiful molded body can be obtained.

[0114] In addition, the composition of the present disclosure can provide a molded body that is excellent in deformation resistance to high temperature and high load, stress crack resistance, deformation resistance to tensile stress, and resistance to repeated stress loads.

[0115] The tensile modulus of the molded article disclosed herein at 105° C. is preferably 50.0 MPa or more, more preferably 51.0 MPa or more, further preferably 53.0 MPa or more, further preferably 54.0 MPa or more, further preferably 55.0 MPa or more, particularly preferably 56.0 MPa or more, and most preferably 57.0 MPa or more. A molded article having a high tensile modulus of elasticity is excellent in deformation resistance to tensile stress.

[0116] The tensile strength of the molded article disclosed herein at 320,000 times is preferably 5.30 N or more, more preferably 5.40 N or more, and further preferably 5.50 N or more. A molded article having a high tensile strength at 320,000 times is excellent in resistance to repeated stress loads.

[0117] As the molded body, for example, nuts, bolts, joints, films, bottles, washers, wire coatings, tubes, hoses, pipes, valves, sheets, seals, gaskets, cans, rollers, containers, stopcocks, connectors, filter housings, filter covers, flow meters, pumps, wafer carriers, wafer boxes, etc. can be used.

[0118] The composition of the present disclosure or the above-mentioned molded article can be used for the following purposes, for example.

[0119] Films for food packaging, lining materials for fluid delivery pipelines used in food manufacturing processes, gaskets, sealing materials, sheets and other fluid delivery components for food manufacturing equipment;

[0120] Chemical plugs, packaging films, lining materials, gaskets, sealing materials, thin plates and other reagent delivery components for fluid delivery pipelines used in chemical manufacturing processes;

[0121] Lining components for the inner surface of reagent tanks and piping in chemical equipment and semiconductor factories;

[0122] O (square) rings / tubes / gaskets, valve core materials, hoses, sealing materials, etc. used in automobile fuel systems and peripheral devices; fuel delivery components such as hoses and sealing materials used in automobile AT devices;

[0123] Flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in car engines and peripheral devices of automobiles; other automobile components such as automobile brake hoses, air conditioning hoses, radiator hoses, wire covering materials, etc.;

[0124] O (square) rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, gaskets, diaphragms, joints and other reagent delivery components for semiconductor manufacturing equipment;

[0125] Coating / ink components such as coating rollers, hoses, tubes, and ink containers for coating equipment;

[0126] Food and beverage conveying components such as tubes or hoses for food and beverages, tubes, hoses, belts, gaskets, joints, etc., food packaging materials, and glass cooking equipment;

[0127] Waste liquid transmission components such as pipes and hoses used for waste liquid transmission;

[0128] Components for high-temperature liquid transmission such as pipes and hoses used for high-temperature liquid transmission;

[0129] Steam piping components such as pipes and hoses used for steam piping;

[0130] Pipe corrosion protection tapes such as tapes wrapped around pipes on ship decks, etc.

[0131] Various covering materials such as wire covering materials, optical fiber covering materials, transparent surface covering materials and back-side agents provided on the light incident side surface of photovoltaic elements of solar cells;

[0132] Diaphragms of diaphragm pumps and sliding components such as various sealing gaskets;

[0133] Weather-resistant covers for agricultural films, various roofing materials, sidewalls, etc.;

[0134] Interior materials used in the construction field, non-combustible fireproof safety glass and other glass covering materials;

[0135] Lining materials for laminated steel sheets used in the home appliance field, etc.

[0136] Further examples of the fuel delivery member used in the fuel system of the above-mentioned automobile include fuel hoses, filler hoses, evaporator hoses, etc. The above-mentioned fuel delivery member can also be used as a fuel delivery member for sour gasoline, alcohol fuel, and fuel added with gasoline additives such as methyl tert-butyl ether resistance and amine resistance.

[0137] The chemical plug and packaging film have excellent chemical resistance to acids, etc. In addition, as the chemical liquid conveying member, there can also be mentioned a corrosion-resistant tape wound around the piping of chemical equipment.

[0138] Examples of the molded article include automobile radiator water chambers, chemical tanks, bellows, partitions, rollers, gasoline tanks, waste liquid transport containers, high temperature liquid transport containers, fisheries and fish farming tanks, and the like.

[0139] Examples of the molded bodies include automobile bumpers, door trims, instrument panels, food processing equipment, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, display screens, liquid crystal display screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, integrated bathrooms, ventilation fans, lighting frames, and the like.

[0140] The molded body can be suitably used as a compressed member such as a gasket or a sealing gasket. The compressed member can be a gasket or a sealing gasket.

[0141] The size and shape of the compressed member can be appropriately set according to the purpose and are not particularly limited. The shape of the compressed member can be, for example, annular. In addition, the compressed member can have a circular, elliptical, rounded quadrilateral or the like shape when viewed from above, and have a through hole in its central portion.

[0142] The compressed member is preferably used as a member for constituting a non-aqueous electrolyte battery. The compressed member is particularly suitable as a member used in a state of contact with the non-aqueous electrolyte in the non-aqueous electrolyte battery. That is, the compressed member may have a liquid contact surface with the non-aqueous electrolyte in the non-aqueous electrolyte battery.

[0143] The nonaqueous electrolyte battery is not particularly limited as long as it is a battery having a nonaqueous electrolyte, and examples thereof include lithium ion secondary batteries, lithium ion capacitors, etc. In addition, members constituting the nonaqueous electrolyte battery include sealing members, insulating members, and the like.

[0144] The non-aqueous electrolyte is not particularly limited, and one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. can be used. The non-aqueous electrolyte battery can further include an electrolyte. The electrolyte is not particularly limited, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc. can be used.

[0145] The compressed member can be preferably used as a sealing member such as a sealing gasket or a sealing pad, or an insulating member such as an insulating gasket or an insulating pad. A sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating member is a member used for electrical insulation. A compressed member can also be a member used for both sealing and insulation purposes.

[0146] The compressed member can be suitably used as a sealing member for nonaqueous electrolyte batteries or an insulating member for nonaqueous electrolyte batteries. In addition, the compressed member has excellent insulating properties because it contains the above-mentioned composition. Therefore, when the compressed member is used as an insulating member, it is firmly fitted with more than two conductive members to prevent short circuits for a long time.

[0147] The composition of the present disclosure can be suitably used as a material for forming an electric wire coating. A coated electric wire having a coating layer containing the composition of the present disclosure is unlikely to deform even when a load is applied in a high-temperature environment.

[0148] The covered electric wire comprises a core wire and a covering layer disposed around the core wire and containing the composition of the present disclosure. For example, an extruded body formed by melt-extruding the composition of the present disclosure on the core wire can be used as the covering layer. The covered electric wire is suitable for LAN cables (Ethernet Cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is suitable for transmission cables such as LAN cables (Ethernet Cables) and high-frequency transmission cables.

[0149] As the material of the core wire, a metal conductor material such as copper or aluminum can be used. The core wire preferably has a diameter of 0.02 mm to 3 mm. The core wire diameter is more preferably 0.04 mm or more, further preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The core wire diameter is more preferably 2 mm or less.

[0150] As specific examples of the core wire, AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 μm), AWG-26 (solid copper wire with a diameter of 404 μm), AWG-24 (solid copper wire with a diameter of 510 μm), AWG-22 (solid copper wire with a diameter of 635 μm), etc. can be used.

[0151] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm, and the thickness of the coating layer is also preferably 2.0 mm or less.

[0152] As a high-frequency transmission cable, a coaxial cable can be cited. A coaxial cable generally has a structure in which an inner conductor, an insulating coating, an outer conductor layer, and a protective coating are sequentially stacked from the core to the periphery. A molded body containing the composition disclosed herein can be suitably used as an insulating coating. The thickness of each layer in the above structure is not particularly limited. Generally, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating coating is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective coating is about 0.5 mm to 2 mm.

[0153] The coating layer may contain air bubbles, and the air bubbles are preferably uniformly distributed in the coating layer.

[0154] The average bubble diameter of the bubbles is not limited, and is, for example, preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less, and particularly preferably 23 μm or less. In addition, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by obtaining an electron microscope image of a cross section of the wire, calculating the diameter of each bubble by image processing, and averaging them.

[0155] The foaming rate of the coating layer may be 20% or more. More preferably, it is 30% or more, further preferably, it is 33% or more, and further preferably, it is 35% or more. The upper limit is not particularly limited, and is, for example, 80%. The upper limit of the foaming rate may be 60%. The foaming rate is a value calculated as ((specific gravity of the wire coating material - specific gravity of the coating layer) / specific gravity of the wire coating material) × 100. The foaming rate can be appropriately adjusted according to the application by, for example, adjusting the amount of gas inserted in the extruder described later, or by selecting the type of dissolved gas.

[0156] The covered electric wire may also have other layers between the core wire and the covering layer, and may further have other layers (outer layers) around the covering layer. When the covering layer contains bubbles, the electric wire may also be a two-layer structure (skin-foam) in which a non-foam layer is inserted between the core wire and the covering layer; a two-layer structure (foam-skin) in which a non-foam layer is covered on the outer layer; and a three-layer structure (skin-foam-skin) in which a non-foam layer is covered on the outer layer of the skin-foam. The non-foam layer is not particularly limited, and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and polyvinyl chloride [PVC].

[0157] The covered electric wire can be produced, for example, by heating the composition using an extruder and extruding the composition in a molten state onto a core wire to form a covering layer.

[0158] When forming the coating, it is also possible to heat the composition, under the state where the composition is molten, introduce gas into the composition, thereby forming the above-mentioned coating containing bubbles. As the gas, for example, a mixture of gases such as difluorochloromethane, nitrogen, carbon dioxide or the above-mentioned gases can be used. The gas can be introduced into the heated composition in the form of pressurized gas, or it can be produced by mixing a chemical foaming agent in the composition. The gas dissolves in the composition in the molten state.

[0159] In addition, the composition of the present disclosure can be suitably used as a material for products for high-frequency signal transmission.

[0160] The high-frequency signal transmission product is not particularly limited as long as it is a product used for the transmission of high-frequency signals, and examples thereof include (1) insulating plates of high-frequency circuits, insulating materials of connecting components, molded plates such as printed wiring boards, (2) molded bodies such as bases and antenna covers of high-frequency vacuum tubes, and (3) coated wires such as coaxial cables and LAN cables. The high-frequency signal transmission product can be suitably used in equipment that utilizes microwaves, particularly 3 GHz to 30 GHz microwaves, such as satellite communication equipment and mobile phone base stations.

[0161] In the above-mentioned high-frequency signal transmission product, the composition of the present disclosure can be suitably used as an insulator because of its low dielectric loss tangent.

[0162] As the above-mentioned (1) molded plate, a printed wiring board is preferred from the aspect of obtaining good electrical characteristics. The above-mentioned printed wiring board is not particularly limited, and examples thereof include printed wiring boards of electronic circuits such as mobile phones, various computers, and communication equipment. As the above-mentioned (2) molded body, a radome is preferred from the aspect of low dielectric loss.

[0163] The compositions of the present disclosure may be suitable for use in films.

[0164] The film is useful as a release film. The release film can be produced by molding the composition of the present disclosure by melt extrusion molding, calendar molding, press molding, cast molding, etc. From the perspective of obtaining a uniform thin film, the release film can be produced by melt extrusion molding.

[0165] It can be applied to the surface of rollers used in OA equipment. In addition, the composition of the present disclosure can be formed into a necessary shape by extrusion molding, compression molding, press molding, etc., and formed into a sheet, film, or tube, and used as a surface material for OA equipment rollers or OA equipment belts, etc. In particular, thin-walled tubes and films can be manufactured by melt extrusion molding.

[0166] The compositions of the present disclosure may also be suitable for use in tubes, bottles, and the like.

[0167] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0168] <1> According to a first aspect of the present disclosure, there is provided a composition comprising polytetrafluoroethylene and a fluorinated copolymer, wherein:

[0169] The content of the polytetrafluoroethylene in the composition is 0.03% to 0.30% by mass relative to the mass of the composition.

[0170] The fluorine-containing copolymer contains tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units.

[0171] The content of the hexafluoropropylene unit in the fluorinated copolymer is 8.5 to 11.2% by mass based on the total monomer units.

[0172] The content of the perfluoro(propyl vinyl ether) unit is 0.5 to 2.0% by mass based on all monomer units, and the melt flow rate at 372° C. is 13.0 to 42.0 g / 10 minutes.

[0173] <2> According to a second aspect of the present disclosure, there is provided the composition according to the first aspect, wherein the content of the hexafluoropropylene units in the fluorinated copolymer is 9.4% by mass to 11.0% by mass based on all monomer units.

[0174] <3> According to a third aspect of the present disclosure, there is provided the composition according to the first aspect or the second aspect, wherein the content of the perfluoro(propyl vinyl ether) unit in the fluorinated copolymer is 0.7 to 1.8% by mass based on all monomer units.

[0175] <4> According to a fourth aspect of the present disclosure, there is provided the composition according to any one of the first to third aspects, wherein the fluorinated copolymer has a melt flow rate at 372° C. of 15.0 to 38.0 g / 10 min.

[0176] <5> According to a fifth aspect of the present disclosure, there is provided a composition according to any one of the first to fourth aspects, wherein the polytetrafluoroethylene has a standard specific gravity of 2.15 to 2.25.

[0177] <6> According to a sixth aspect of the present disclosure, there is provided a composition according to any one of the first to fifth aspects, wherein a content of the polytetrafluoroethylene in the composition is 0.05% by mass to 0.20% by mass based on the mass of the composition.

[0178] <7> According to a seventh aspect of the present disclosure, there is provided an injection-molded article including the composition according to any one of the first to sixth aspects.

[0179] <8> According to an eighth aspect of the present disclosure, there is provided a powder coating material including the composition according to any one of the first to sixth aspects.

[0180] <9> According to a ninth aspect of the present disclosure, there is provided a covered electric wire including a covering layer containing the composition according to any one of the first to sixth aspects.

[0181] Example

[0182] Next, the embodiments of the present disclosure will be described with reference to experimental examples, but the present disclosure is not limited to the experimental examples.

[0183] Each numerical value of the experimental example was measured by the following method.

[0184] (Content of monomer units)

[0185] The content of each monomer unit of the fluorinated copolymer is measured using an NMR analyzer (for example, AVANCE300 high temperature probe manufactured by Bruker BioSpin) or an infrared absorption analyzer (Spectrum One manufactured by Perkin Elmer).

[0186] (Melt Flow Rate (MFR))

[0187] The MFR of the fluorinated copolymer was determined by measuring the mass (g / 10 minutes) of the polymer flowing out from a die having an inner diameter of 2 mm and a length of 8 mm at 372°C and a load of 5 kg using a melt flow indexer G-01 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ASTM D-1238.

[0188] (Amount of -CF2H)

[0189] The number of -CF2H groups in the fluorinated copolymer was measured using a nuclear magnetic resonance apparatus AVANCE-300 (manufactured by Bruker BioSpin) at a temperature of (melting point of the polymer + 20)°C. 19 In F-NMR measurement, it was determined from the peak integral value of -CF2H group.

[0190] (Amount of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2)

[0191] The dry powder or pellets obtained in the experimental example are formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.3 mm. The film is scanned 40 times by a Fourier transform infrared spectrometer [FT-IR (Spectrum One, manufactured by PerkinElmer)] and analyzed to obtain an infrared absorption spectrum. The obtained infrared absorption spectrum is compared with the infrared absorption spectrum of a known film to determine the type of terminal group. In addition, the absorption peak of a specific functional group that appears in the differential spectrum between the obtained infrared absorption spectrum and the infrared absorption spectrum of a known film is calculated according to the following formula (A) for every 1×10 6 The number of functional groups N per carbon atom.

[0192] N=I×K / t(A)

[0193] I: Absorbance

[0194] K: Correction coefficient

[0195] t: film thickness (mm)

[0196] For reference, the absorption frequency, molar absorption coefficient and correction coefficient of the functional groups in the experimental examples are shown in Table 2. The molar absorption coefficient was determined from the FT-IR measurement data of the low molecular model compound.

[0197] [Table 2]

[0198] Table 2

[0199]

[0200] (-OC(=O)OR(carbonate group) number)

[0201] The analysis was performed using the method described in International Publication No. 2019 / 220850. The absorption frequency was set to 1817 cm -1 The number of -OC(=O)OR (carbonate groups) was calculated in the same manner as the method for calculating the number of functional groups N, except that the molar absorptivity was set to 170 (l / cm / mol) and the correction factor was set to 1426.

[0202] (Melting point of fluorinated copolymer)

[0203] Regarding the melting point of the fluorinated copolymer, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science Co., Ltd.) was used to perform the first temperature increase from 200°C to 350°C at a temperature increase rate of 10°C / min, then cooled from 350°C to 200°C at a cooling rate of 10°C / min, and then the second temperature increase from 200°C to 350°C was performed again at a temperature increase rate of 10°C / min. The melting point was determined from the peak of the melting curve generated in the second temperature increase process.

[0204] (Standard specific gravity)

[0205] The standard specific gravity of PTFE is measured by a water displacement method in accordance with ASTM D 792 using a sample molded in accordance with ASTM D4895-89.

[0206] (Melting point of PTFE)

[0207] Regarding the melting point of PTFE, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-TechScience) was used to heat the sample from 230°C to 380°C for the first time at a heating rate of 10°C / min, then the sample was cooled from 380°C to 230°C at a cooling rate of 10°C / min, and then the sample was heated from 230°C to 380°C for the second time at a heating rate of 10°C / min. The melting point was determined from the peak of the melting curve generated during the second heating process.

[0208] (Average primary particle size)

[0209] For an aqueous dispersion containing PTFE diluted with water to a solid content of 0.22% by mass, the transmittance of projected light with a wavelength of 500 nm relative to a unit length is measured. The oriented diameter in the transmission electron microscope photograph is measured in advance and can be determined based on a calibration curve of the obtained PTFE number-based length average primary particle size and the above-mentioned transmittance.

[0210] In Experimental Examples 1 to 17, 20, and 21, the following aqueous dispersions of PTFE were used.

[0211] Aqueous dispersion containing PTFE

[0212] PTFE: TFE homopolymer with fibrillation and non-melt processability

[0213] Standard specific gravity of PTFE: 2.173

[0214] Melting point of PTFE: 327°C

[0215] Average primary particle size of PTFE: 300nm

[0216] Solid content: 30% by mass

[0217] Experimental Example 1

[0218] According to the production method described in Japanese Patent Application Laid-Open No. 2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of a TFE / HFP / PPVE copolymer (FEP) having a solid content concentration of 20.5% by mass.

[0219] In this FEP aqueous dispersion, the aqueous dispersion of PTFE was added and mixed in a manner such that the ratio of the PTFE solid component to the solid component in the aqueous dispersion was 0.50 mass %, and then water and 60% nitric acid were added and stirred to precipitate the mixture, and after the solid phase was separated from the liquid phase, moisture was removed. After washing with deionized water, the obtained white powder was dried at 200° C. for 60 hours to obtain a powder.

[0220] (Pelletization)

[0221] The obtained powder was melt-extruded at 385° C. using a twin-screw extruder (KZW15TW-60MG-NH-700, manufactured by TECHNOVEL) to obtain pellets. The content of each monomer unit of FEP in the obtained pellets was measured using the obtained pellets. The results are shown in Table 3.

[0222] (Fluorination)

[0223] After degassing the obtained pellets at 200°C in an electric furnace for 72 hours, they were placed in a vacuum vibration reactor VVD-30 (manufactured by Ohkawara Manufacturing Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted with N2 gas to 20% by volume was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, the system was temporarily evacuated and F2 gas was introduced again. Further, 0.5 hours later, the system was evacuated again and F2 gas was introduced again. After that, the above-mentioned F2 gas introduction and evacuation operations were continued once every 1 hour, and the reaction was carried out at a temperature of 200°C for 8 hours. After the reaction was completed, the reactor was fully replaced with N2 gas to terminate the fluorination reaction and obtain pellets. Using the obtained pellets, the MFR, melting point and number of functional groups of FEP in the pellets were measured. The results are shown in Table 3.

[0224] Experimental Example 2

[0225] According to the production method described in Japanese Patent Application Laid-Open No. 2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of a TFE / HFP / PPVE copolymer (FEP) having a solid content concentration of 20.5% by mass.

[0226] In this FEP aqueous dispersion, the aqueous dispersion of PTFE was added and mixed in a manner such that the ratio of the PTFE solid component to the solid component in the aqueous dispersion was 0.06 mass %, and then water and 60% nitric acid were added and stirred to precipitate the solid phase and the liquid phase, and then the water was removed. After washing with deionized water, the obtained white powder was dried at 200° C. for 60 hours to obtain a powder.

[0227] (Pelletization)

[0228] The obtained powder was melt-extruded at 370°C using a twin-screw extruder (KZW15TW-60MG-NH-700, manufactured by TECHNOVEL) to obtain pellets of a fluororesin composition. The content of each monomer unit of FEP in the obtained pellets was measured using the obtained pellets. The results are shown in Table 3.

[0229] (Fluorination)

[0230] The obtained pellets were fluorinated in the same manner as in Experimental Example 1. The obtained pellets were used to measure the MFR, melting point, and number of functional groups of FEP in the pellets. The results are shown in Table 3.

[0231] Experimental Example 3

[0232] After mixing 86 parts by mass of the pellets prepared in Experimental Example 2 and 14 parts by mass of the pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345° C. using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets having a PTFE content of 0.12% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0233] Experimental Example 4

[0234] According to the production method described in Japanese Patent Application Laid-Open No. 2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of a TFE / HFP / PPVE copolymer (FEP) having a solid content concentration of 20.5% by mass.

[0235] In this FEP aqueous dispersion, the aqueous dispersion of PTFE was added and mixed in a manner such that the ratio of the PTFE solid component to the solid component in the aqueous dispersion was 0.07 mass %, and then water and 60% nitric acid were added and stirred to precipitate the mixture, and after the solid phase was separated from the liquid phase, moisture was removed. After washing with deionized water, the obtained white powder was dried at 200° C. for 60 hours to obtain a powder.

[0236] (Pelletization)

[0237] The obtained powder was molded into pellets (wet heat treatment) by the method described in paragraph 0058 of Example 1 of International Publication No. 2006 / 123694. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0238] Experimental Example 5

[0239] According to the production method described in JP-A-2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of the copolymer (FEP).

[0240] Water and 60% nitric acid were added to the FEP aqueous dispersion and stirred to precipitate, and after the solid phase and the liquid phase were separated, the water was removed, and the obtained white powder was washed with deionized water and dried at 200° C. for 60 hours to obtain a powder.

[0241] (Pelletization)

[0242] The obtained powder was extruded into pellets by the method of Experimental Example 2. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets. The results are shown in Table 3.

[0243] (Fluorination)

[0244] The obtained pellets were fluorinated in the same manner as in Experimental Example 1. The obtained pellets were used to measure the MFR, melting point, and number of functional groups of FEP in the pellets. The results are shown in Table 3.

[0245] Experimental Example 6

[0246] According to the production method described in Japanese Patent Application Laid-Open No. 2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of a TFE / HFP / PPVE copolymer (FEP) having a solid content concentration of 20.5% by mass.

[0247] In this FEP aqueous dispersion, the aqueous dispersion of PTFE was added and mixed in a manner such that the ratio of the PTFE solid component to the solid component in the aqueous dispersion was 0.07 mass %, and then water and 60% nitric acid were added and stirred to precipitate the mixture, and after the solid phase was separated from the liquid phase, moisture was removed. After washing with deionized water, the obtained white powder was dried at 200° C. for 60 hours to obtain a powder.

[0248] (Pelletization)

[0249] The obtained powder was extruded into pellets by the method of Experimental Example 2. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets. The results are shown in Table 3.

[0250] (Fluorination)

[0251] The obtained pellets were fluorinated in the same manner as in Experimental Example 1. The obtained pellets were used to measure the MFR, melting point, and number of functional groups of FEP in the pellets. The results are shown in Table 3.

[0252] Experimental Example 7

[0253] After mixing 82 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 18 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.09% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0254] Experimental Example 8

[0255] Pellets were obtained by the method of Example 1 of International Publication No. 2009 / 044753. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0256] Experimental Example 9

[0257] Pellets were obtained by the method of Example 1 of International Publication No. 2006 / 123694. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0258] Experimental Example 10

[0259] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0260] Experimental Example 11

[0261] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0262] Experimental Example 12

[0263] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0264] Experimental Example 13

[0265] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0266] Experimental Example 14

[0267] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0268] Experimental Example 15

[0269] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0270] Experimental Example 16

[0271] After mixing 86 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 14 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.07% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0272] Experimental Example 17

[0273] After mixing 90 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 10 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.05% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0274] Experimental Example 18

[0275] In Experimental Example 18, PTFE aqueous dispersion 2 was used.

[0276] PTFE aqueous dispersion 2

[0277] PTFE: TFE homopolymer with fibrillation and non-melt processability

[0278] Standard specific gravity of PTFE: 2.200

[0279] Melting point of PTFE: 327°C

[0280] Average primary particle size of PTFE: 300nm

[0281] Solid content: 30% by mass

[0282] According to the production method described in Japanese Patent Application Laid-Open No. 2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of a TFE / HFP / PPVE copolymer (FEP) having a solid content concentration of 20.5% by mass.

[0283] In this FEP aqueous dispersion, PTFE aqueous dispersion 2 was added and mixed in such a manner that the ratio of PTFE solid content to the solid content in the aqueous dispersion became 0.20 mass %, and then water and 60% nitric acid were added and stirred to precipitate, and after the solid phase was separated from the liquid phase, moisture was removed. After washing with deionized water, the obtained white powder was dried at 200° C. for 60 hours to obtain a powder.

[0284] (Pelletization)

[0285] The obtained powder was melt-extruded at 375°C using a twin-screw extruder (KZW15TW-60MG-NH-700, manufactured by TECHNOVEL) to obtain pellets of a fluororesin composition. The content of each monomer unit of FEP in the obtained pellets was measured using the obtained pellets. The results are shown in Table 3.

[0286] (Fluorination)

[0287] The obtained pellets were fluorinated in the same manner as in Experimental Example 1. The obtained pellets were used to measure the MFR, melting point, and number of functional groups of FEP in the pellets. The results are shown in Table 3.

[0288] Experimental Example 19

[0289] In Experimental Example 19, PTFE aqueous dispersion 3 was used.

[0290] PTFE aqueous dispersion 3

[0291] PTFE: PTFE with fibrillation and non-melt processability, containing 0.1 mass% of PPVE (modified PTFE)

[0292] Standard specific gravity of PTFE: 2.159

[0293] Melting point of PTFE: 324°C

[0294] Average primary particle size of PTFE: 300nm

[0295] Solid content: 30% by mass

[0296] According to the production method described in Japanese Patent Application Laid-Open No. 2010-235667, the reaction scale, reaction pressure, TFE input amount, HFP input amount, PPVE input amount, ammonium persulfate input amount, etc. were appropriately adjusted to prepare an aqueous dispersion of a TFE / HFP / PPVE copolymer (FEP) having a solid content concentration of 20.5% by mass.

[0297] In this FEP aqueous dispersion, PTFE aqueous dispersion 3 was added and mixed in such a manner that the ratio of PTFE solid content to the solid content in the aqueous dispersion became 0.15 mass %, and then water and 60% nitric acid were added and stirred to precipitate, and after the solid phase and the liquid phase were separated, water was removed. After washing with deionized water, the obtained white powder was dried at 200° C. for 60 hours to obtain a powder.

[0298] (Pelletization)

[0299] The obtained powder was melt-extruded at 375°C using a twin-screw extruder (KZW15TW-60MG-NH-700, manufactured by TECHNOVEL) to obtain pellets of a fluororesin composition. The content of each monomer unit of FEP in the obtained pellets was measured using the obtained pellets. The results are shown in Table 3.

[0300] (Fluorination)

[0301] After degassing the obtained pellets at 200°C in an electric furnace for 72 hours, the pellets were placed in a vacuum vibration reactor VVD-30 (manufactured by Ohkawara Manufacturing Co., Ltd.) and heated to 170°C. After evacuation, F2 gas diluted with N2 gas to 20% by volume was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, the gas was temporarily evacuated and F2 gas was introduced again. Further, 0.5 hours later, the gas was evacuated again and F2 gas was introduced again. After that, the above-mentioned F2 gas introduction and evacuation operations were continued once for 1 hour, and the reaction was carried out at a temperature of 170°C for 6 hours. After the reaction was completed, the reactor was fully replaced with N2 gas, the fluorination reaction was terminated, and pellets were obtained. Using the obtained pellets, the MFR, melting point, and number of functional groups of FEP in the pellets were measured. The results are shown in Table 3.

[0302] Experimental Example 20

[0303] After mixing 90 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 10 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.05% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0304] Experimental Example 21

[0305] After mixing 90 parts by mass of pellets of fluorinated TFE / HFP / PPVE copolymer (FEP) and 10 parts by mass of pellets prepared in Experimental Example 1, the pellets were melt-extruded at 345°C using a twin-screw extruder (Laboplasto Mill 30C-150, manufactured by Toyo Seiki Co., Ltd.) to obtain pellets of a fluororesin composition having a PTFE content of 0.05% by mass. The obtained pellets were used to measure the content of each monomer unit of FEP in the pellets, MFR, melting point, and number of functional groups. The results are shown in Table 3.

[0306] Next, reference examples of methods for producing copolymers are shown. The copolymers described in the reference examples are not included in the embodiments of the composition disclosed herein.

[0307] Reference Example 1

[0308] 40.25 kg of deionized water and 0.099 kg of methanol were added to an autoclave with a stirrer of a volume of 174 L, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 40.25 kg of HFP and 0.36 kg of PPVE were added to the autoclave in a vacuum state, and the autoclave was heated to 30.0 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.905 MPa, and then 0.63 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.905 MPa, and the set pressure was maintained by continuously adding TFE. 0.099 kg of methanol was added 1.5 hours after the start of polymerization. 2 hours and 4 hours after the start of polymerization, 0.63 kg of DHP was added and the internal pressure was reduced by 0.001 MPa. 6 hours later, 0.48 kg was added and the internal pressure was reduced by 0.001 MPa. Thereafter, 0.13 kg of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.

[0309] It should be noted that 0.11 kg of PPVE was added when the continuous additional input amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.099 kg of methanol was added to the autoclave when the additional input amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional input amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. After that, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 46.2 kg of dry powder.

[0310] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. Various physical properties were measured using the obtained pellets by the above-mentioned methods. The results are shown in Table 3.

[0311] Reference Example 2

[0312] The amount of methanol added before the start of polymerization was changed to 0.067 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.067 kg, the amount of PPVE added before the start of polymerization was changed to 0.36 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.11 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.906 MPa. Copolymer pellets were obtained in the same manner as in Reference Example 1. Various physical properties were measured using the obtained pellets by the above-mentioned methods. The results are shown in Table 3.

[0313] Reference Example 3

[0314] 40.25 kg of deionized water and 0.195 kg of methanol were added to an autoclave with a stirrer of 174 L volume, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 40.25 kg of HFP was added to the autoclave in a vacuum state, and the autoclave was heated to 30.0 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.926 MPa, and then 0.63 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.926 MPa, and the set pressure was maintained by continuously adding TFE. 0.195 kg of methanol was added 1.5 hours after the start of polymerization. 2 hours and 4 hours after the start of polymerization, 0.63 kg of DHP was added and the internal pressure was reduced by 0.001 MPa. 6 hours later, 0.48 kg was added and the internal pressure was reduced by 0.001 MPa. Thereafter, 0.13 kg of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.

[0315] In addition, 0.195 kg of methanol was added to the autoclave when the additional amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional amount of TFE reached 40.25 kg. After the polymerization was completed, unreacted TFE and HFP were released to obtain a wet powder. Thereafter, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 45.2 kg of dry powder.

[0316] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. The HFP content and PPVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.

[0317] Reference Example 4

[0318] The amount of methanol added before the start of polymerization was changed to 0.274 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.274 kg, the amount of PPVE added before the start of polymerization was changed to 0.41 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.11 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.937 MPa. Copolymer pellets were obtained in the same manner as in Reference Example 1. Various physical properties were measured using the obtained pellets by the above-mentioned methods. The results are shown in Table 3.

[0319] Reference Example 5

[0320] 40.25kg of deionized water and 0.189kg of methanol were added to an autoclave with a stirrer of a volume of 174L, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 40.25kg of HFP and 0.42kg of PPVE were added to the autoclave in a vacuum state, and the autoclave was heated to 25.5°C. Next, TFE was added until the internal pressure of the autoclave reached 0.830MPa, and then 1.25kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.830MPa, and the set pressure was maintained by continuously adding TFE. 0.189kg of methanol was added 1.5 hours after the start of polymerization. 1.25 kg of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002 MPa. 0.96 kg was added 6 hours later, and the internal pressure was reduced by 0.002 MPa. Thereafter, 0.25 kg of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.002 MPa each time.

[0321] It should be noted that 0.11 kg of PPVE was added when the continuous additional input amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.189 kg of methanol was added to the autoclave when the additional input amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional input amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. After that, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 45.4 kg of dry powder.

[0322] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. Various physical properties were measured using the obtained pellets by the above-mentioned methods. The results are shown in Table 3.

[0323] Reference Example 6

[0324] The amount of methanol added before the start of polymerization was changed to 0.128 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.128 kg, the amount of PPVE added before the start of polymerization was changed to 0.46 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.12 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.832 MPa. Copolymer pellets were obtained in the same manner as in Reference Example 5. Various physical properties were measured using the obtained pellets by the above-mentioned methods. The results are shown in Table 3.

[0325] Reference Example 7

[0326] The amount of methanol added before the start of polymerization was changed to 0.206 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.206 kg, the amount of PPVE added before the start of polymerization was changed to 0.35 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.11 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.897 MPa. Copolymer pellets were obtained in the same manner as in Reference Example 1. Various physical properties were measured using the obtained pellets by the above-mentioned methods. The results are shown in Table 3.

[0327]

[0328]

[0329] "Others (pcs / C10)" in Table 3 6 The record of "<9" in Table 3 means that the number (total number) of -CF2H groups is less than 9. The record of "<6" in Table 3 means that the number (total number) of the target functional groups is less than 6. The record of "ND" in Table 3 means that the peak for the target functional group cannot be confirmed to a quantitative degree.

[0330] Next, the following properties were evaluated using the obtained pellets. The results are shown in Table 4.

[0331] 1. Manufacturing of tablets

[0332] The pellets were injection molded using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., SE50EV-A) with the barrel temperature set to 380°C, the mold temperature set to 170°C, and the injection speed set to 5 mm / s. As the mold, a mold made of HPM38 (100 mm×100 mm×2.0 mmt, side gate) was used. When removing, the injection molded body was ejected by the ejector pin to drop from the mold and recovered using the chute directly below the mold.

[0333] 1-1. Flow marks

[0334] The injection molded product was visually observed and evaluated based on the following criteria.

[0335] 0: No flow marks

[0336] ×: Flow marks

[0337] 1-2. Stripes

[0338] 10 injection molded articles were observed to see if there were fibrous streaks. Fiber-like streaks are caused by stringing (molding defects) generated during molding.

[0339] ○: All 10 injection molded bodies have no fibrous streaks

[0340] ×: One or more injection molded articles have fibrous streaks

[0341] 1-3. Scratches

[0342] The injection molded article immediately after being recovered from the chute was visually observed and evaluated based on the following criteria.

[0343] ○: No scratches caused by friction

[0344] ×: There are scratches caused by friction

[0345] 1-4. Layering

[0346] The injection molded article was visually observed and delamination was evaluated according to the following criteria.

[0347] ○: The surface is not rough due to peeling of the surface layer.

[0348] ×: Roughness due to peeling (delamination) of the surface layer was observed on the surface.

[0349] 1-5. Mold release

[0350] The molding was continued for 10 times, and the number of times the injection molded body did not fall from the mold due to the ejection of the ejector pin was checked.

[0351] ○: 0 times

[0352] ×: 1 to 10 times

[0353] 3.113℃ load deformation evaluation

[0354] The pellets were used to make a sheet with a thickness of 0.5 mm by hot pressing, and a sample with a width of 2.0 mm and a length of 20 mm was made from the obtained sheet. The prepared sample was mounted on a measuring fixture so that the distance between the fixtures was about 10 mm, and a TMA-7100 manufactured by Hitachi High-Technologies Corporation was used. After the sample was heated to 113°C, 4.37 N / mm was applied to the sample. 2of load and left for 900 minutes.

[0355] The difference between the ratio (%) obtained by dividing the sample length at 80 minutes after the start of load application by the initial sample length and the ratio (%) obtained by dividing the sample length at 855 minutes after the start of load application by the initial sample length was calculated as the deformation rate (%).

[0356] The deformation rate (%) is a value indicating how much deformation has occurred between 80 minutes and 855 minutes. A sample with a small deformation rate (%) is unlikely to deform even when a load is applied in a high temperature environment.

[0357] Deformation rate (%) = X2 / X0×100-X1 / X0×100

[0358] X0: initial sample length

[0359] X1: Sample length at 80 minutes after the start of load application (mm)

[0360] X2: Sample length at 855 minutes after the start of load application (mm)

[0361] 4. Resistance to stress cracking at high temperatures

[0362] Using pellets and a hot press molding machine, a molded body with a thickness of about 2 mm was made. Using a rectangular dumbbell of 13.5 mm × 38 mm, the obtained piece was punched to obtain 3 test pieces. In the center of the long side of each obtained test piece, a 19 mm × 0.45 mm blade was used to cut an incision according to ASTM D1693. Three incision test pieces and 25 g of a 3 mass % aqueous solution of hydrogen peroxide were placed in a 100 mL polypropylene bottle, and after heating at 80 ° C for 20 hours in an electric furnace, the incision test piece was taken out. The three obtained incision test pieces were installed in a stress crack test fixture according to ASTM D1693, and after heating at 80 ° C for 2 hours in an electric furnace, the incision and its surroundings were visually observed to count the number of cracks. Even if the sheet is immersed in a liquid medicine at high temperature and does not produce cracks, it has excellent stress crack resistance at high temperatures.

[0363] ○: The number of cracks is 0

[0364] ×: The number of cracks is 1 or more

[0365] 5. Tensile elastic modulus

[0366] The pellets and the hot press molding machine were used to obtain a 2.0 mm thick test piece (compression molding). A dumbbell-shaped test piece was cut from the test piece using an ASTM V-type dumbbell, and the obtained dumbbell-shaped test piece was used to measure the tensile modulus at 105° C. under the conditions of 50 mm / min using Autograph (AG-I 300 kN manufactured by Shimadzu Corporation) according to ASTM D638. A sheet with a high tensile modulus has excellent deformation resistance to tensile stress.

[0367] Tensile strength at 63,200 cycles

[0368] Using pellets and a hot press molding machine, a sheet with a thickness of about 2.4 mm was made, and using ASTM D1708 micro dumbbells, dumbbell-shaped samples (thickness 2.4 mm, width 5.0 mm, and measurement section length 22 mm) were made. Using a fatigue testing machine MMT-250NV-10 manufactured by Shimadzu Corporation, the sample was mounted on a measuring fixture, and the measuring fixture was set in a constant temperature bath at 110°C with the sample mounted. The tensile strength at 320,000 cycles (tensile strength at a stroke of +0.2 mm, unit: N) was measured by repeatedly stretching in a uniaxial direction with a stroke of 0.2 mm and a frequency of 100 Hz.

[0369] 7. Preparation and evaluation of powder coatings

[0370] After the obtained pellets are crushed, they are sieved with a No. 18 sieve (manufactured by Tokyo Screen Co., Ltd.) to obtain copolymer powder. After the copolymer powder is applied to a degreased SUS316 substrate (200mm×200mm×5mm) with a smooth surface by electrostatic coating, it is vertically hung in a drying furnace and fired at 285°C for 30 minutes to obtain a coating with a film thickness of about 100μm. The obtained coating is visually observed to evaluate the production state of the coating. In addition, it is immersed in water together with the coating, heated at 95°C for 20 hours, and the coating peeled off from the SUS316 substrate is recovered, and the film thickness is measured to confirm that it can be produced with a film thickness within 100μm±20%.

[0371] The obtained coating films were evaluated according to the following criteria.

[0372] ○: A good coating film can be produced

[0373] ×: Unable to produce a good coating film

[0374] Experimental Example 1: It is impossible to produce a coating film with a smooth surface

[0375] Experimental Example 10: Incomplete melting, unable to produce coating film

[0376] Experimental Example 11: The target film thickness cannot be produced due to dripping

[0377] Experimental Example 12: It is impossible to produce a coating film with a smooth surface

[0378] 8. Production and evaluation of covered electric wires

[0379] (Wire coating molding conditions)

[0380] use A wire coating molding machine (manufactured by TANABE PLASTIC MACHINERY CO., LTD.) was used to extrusion coat a conductor having a conductor diameter of 0.50 mm with the following coating thickness to obtain a coated wire. The wire coating extrusion molding conditions were as follows.

[0381] a) Core conductor: soft steel wire conductor diameter 0.50mm

[0382] b) Coating thickness: 0.15mm

[0383] c) Diameter of coated wire: 0.80mm

[0384] d) Wire pulling speed: 100m / min

[0385] e) Extrusion conditions:

[0386] · Single screw extruder with barrel diameter = 30mm, L / D = 22

[0387] Die head (inner diameter) / sheet (outer diameter) = 9.0mm / 5.0mm

[0388] The set temperatures of the extruder were: barrel C-1 (320°C), barrel C-2 (350°C), barrel C-3 (375°C), head H (390°C), die head D-1 (390°C), die head D-2 (390°C). The core wire preheating was set to 80°C.

[0389] The results of the electric wire coating were evaluated according to the following criteria.

[0390] ○: Can produce covered electric wires

[0391] ×: Cannot produce covered electric wire

[0392] Experimental Example 1: The outer diameter has a large deviation and cannot be manufactured

[0393] Experimental Example 10: Production failed due to coating fracture

[0394] Experimental Example 11: The outer diameter has a large deviation and cannot be manufactured

[0395] Experimental Example 12: Production failed due to coating fracture

[0396] Experimental Example 13: Production failed due to coating fracture

[0397] (Confirmation of outer diameter)

[0398] The outer diameter was measured continuously for 10 minutes using an outer diameter measuring instrument (ODAC18XY manufactured by Zumbach). The maximum and minimum outer diameters were rounded to the third decimal place relative to the target outer diameter of 0.90 mm. If the deviation was 3% or more, it was considered that the covered electric wire could not be manufactured.

[0399] (Evaluation of 110°C load deformation of electric wire coating)

[0400] The coating layer of the coated wire obtained above was peeled off, and a sample with a width of about 2 mm and a length of 22 mm was prepared from the obtained coating layer. The prepared sample was mounted on a measuring fixture so that the distance between the fixtures was about 10 mm, and a TMA-7100 manufactured by Hitachi High-Technologies Corporation was used. After the sample was heated to 110°C, a 4.49 N / mm 2 of load and left for 900 minutes.

[0401] The difference between the ratio (%) obtained by dividing the sample length at 85 minutes after the start of load application by the initial sample length and the ratio (%) obtained by dividing the sample length at 900 minutes after the start of load application by the initial sample length was calculated as the deformation rate (%).

[0402] The deformation rate (%) is a value indicating how much deformation has occurred between 85 minutes and 900 minutes. A sample with a small deformation rate (%) is unlikely to deform even when a load is applied in a high temperature environment.

[0403] Deformation rate (%) = X2 / X0×100-X1 / X0×100

[0404] X0: initial sample length

[0405] X1: Sample length at 85 minutes after the start of load application (mm)

[0406] X2: Sample length at 900 minutes after the start of load application (mm)

[0407]

[0408] The copolymers of Reference Examples 1 to 7 are not included in the embodiments of the composition disclosed herein. The copolymers of Reference Examples 1 to 7 can be molded to obtain a film or a tube. In addition, the copolymers of Reference Examples 1 to 7 can also be used for covering electric wires. As the core wire of the covered electric wire, a single wire, a twisted wire, etc. can be used, and any conductor such as a copper wire, a silver-plated wire, etc. can be used.

[0409] (Film Forming)

[0410] use The film was produced using an extruder (manufactured by Imoto Seisakusho) with a T-die. The extrusion molding conditions were as follows.

[0411] a) Winding speed: 1m / min

[0412] b) Roller temperature: 120°C

[0413] c) Film width: 70mm

[0414] d)Thickness: 0.10mm

[0415] e) Extrusion conditions:

[0416] · Single screw extruder with barrel diameter = 14mm, L / D = 20

[0417] Extruder set temperature: barrel C-1 (330°C), barrel C-2 (350°C), barrel C-3 (365°C), T-die head (370°C)

[0418] The results are shown in Table 5.

[0419] (Tube Forming)

[0420] use An extruder (manufactured by Tanabe Plastic Machinery Co., Ltd.) was used to extrude a tube having an outer diameter of 10.0 mm and a wall thickness of 1.0 mm. The extrusion molding conditions were as follows.

[0421] a) Die head inner diameter: 25mm

[0422] b) Spindle outer diameter: 13mm

[0423] c) Inner diameter of shaping die: 10.5mm

[0424] d) Traction speed: 0.4m / min

[0425] e) Outer diameter: 10.0mm

[0426] f) Wall thickness: 1.0mm

[0427] g) Extrusion conditions:

[0428] · Single screw extruder with barrel diameter = 30mm, L / D = 22

[0429] Extruder set temperature: barrel C-1 (350°C), barrel C-2 (370°C), barrel C-3 (380°C), head H-1 (390°C), die head D-1 (390°C), die head D-2 (390°C)

[0430] The results are shown in Table 5.

[0431] [Table 5]

[0432] Table 5

[0433]

Claims

1. A composition comprising polytetrafluoroethylene and a fluorine-containing copolymer, wherein: The content of the polytetrafluoroethylene in the composition is 0.03 mass % to 0.30 mass % relative to the mass of the composition. The fluorine-containing copolymer contains tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units, The content of the hexafluoropropylene unit in the fluorinated copolymer is 8.5 to 11.2% by mass based on the total monomer units. The content of the perfluoro(propyl vinyl ether) unit is 0.5% to 2.0% by mass based on the total monomer units. The melt flow rate at 372°C is 13.0 g / 10 min to 42.0 g / 10 min.

2. The composition according to claim 1, wherein The content of the hexafluoropropylene unit in the fluorinated copolymer is 9.4 to 11.0 mass % based on the total monomer units.

3. The composition according to claim 1 or 2, wherein The content of the perfluoro(propyl vinyl ether) unit in the fluorinated copolymer is 0.7 to 1.8 mass % based on the total monomer units.

4. The composition according to any one of claims 1 to 3, wherein The melt flow rate of the fluorine-containing copolymer at 372° C. is 15.0 g / 10 min to 38.0 g / 10 min.

5. The composition according to any one of claims 1 to 4, wherein The standard specific gravity of the polytetrafluoroethylene is 2.15 to 2.

25.

6. The composition according to any one of claims 1 to 5, wherein The content of the polytetrafluoroethylene in the composition is 0.05% by mass to 0.20% by mass based on the mass of the composition. 7 . An injection-molded article comprising the composition according to claim 1 .

8. A powder coating comprising the composition according to any one of claims 1 to 6. 9 . A covered electric wire comprising a covering layer comprising the composition according to claim 1 .

Citation Information

Patent Citations

  • Method for producing fluorine-containing polymer

    JP2010235667A

  • Fluororesin composition and electric wire

    WO2006123694A1

  • Fluororesin composition and covered electric wire

    WO2009044753A1

  • Layered body and tube

    WO2019220850A1